O23 'A TOAST to team work': the impact of team obstetrics and anaesthetics simulation training on attitudes to effective team work. (November 2018) - Egbase, Elizabeth; Ferns, Janis; Kandasarmy, Gomathy; Murray, Fiona; Hall-Jackson, Megan
Abstract : Introduction: Simulation training has been shown to be an effective way to train health professionals for critical events and improve clinical outcomes in Obstetrics and Gynaecology. Team based training affords individuals the opportunity to acquire and transfer new knowledge, skills and attitudes in an enhanced learning environment. Effective simulation-based team training enables critical reflection of practice and active experimentation as part of the team thus facilitating the application of these new frames in a safe yet realistic environment. Method: The Team Obstetric and Anaesthetic Simulation Training (TOAST) course was based on the team STEPPs model of team work. This prioritises training in established MDTs and our course aims to integrate Obstetric Multidisciplinary team members working together in our hospital. The one-day course consists of workshops on team training, team games and simulation scenarios of evolving crises in intrapartum care. Continuous group debriefing occurs throughout with emphasis on team dynamics, and strategies for optimum team work applicable to the obstetric Multidisciplinary Team. Pre-and post-course questionnaire were used to evaluate the participants views on team work and its implication on their clinical practice. Results: Using the validated Attitude to Healthcare Teams Scale questionnaire in conjunction with Team Skills Scale questionnaire we identified impactful changes in attitudes towards healthcare teams amongst the course participants. Importantly the biggest change came in attitudes toward teams' function and quality of care. Post course 78% of candidates strongly agreed with the statement 'give and take amongst team members help make better patient care decision' compared to only 30% pre-course. There were also positive changes in attitudes towards shared leadership and team efficiency. Improvements were also seen in the post course self-evaluation 67% rated their ability to intervene effectively to improve team function as good or better, compared to 40% pre-course. Discussion: The TOAST course is a valued addition to the multidisciplinary training and has served to challenge participants frameworks and attitudes toward team working. Much emphasis is placed on learning within one's community of practice and this course facilitates learning in socio-cultural context of the team they work in daily. Our results show that implementing specific team based training within the real multidisciplinary team empowers participants. We propose long term follow up of participants to identify any resulting change in behaviours and it connection with clinical outcomes and patient safety. References: Draycot T, Sibanda T, Owen L, et al . Does training in obstetric emergencies improve neonatal outcome? Br J Obs Gynaecol 2006;113:177–82. Johanson R, Cox C, O'Donnell E, et al . Managing obstetric emergencies and trauma (MOET). Structured skills training using models and reality based scenarios. The Obstetrician and Gynaecologist 1999;1:46–52. Lave J, Wenger E. Situated learning: Legitimate peripheral participation 1991. Cambridge & New York: Cambridge University Press. King HB, Battles J, Baker DP, et al. TeamSTEPPS™: Team strategies and tools to enhance performance and patient safety. In: Henriksen K, Battles JB, Keyes MA, Grady ML (eds.), Advances in Patient Safety: New Directions and Alternative Approaches (Vol. 3: Performance and Tools) 2008. Rockville, MD: Agency for Healthcare Research and Quality (US).